Owner of Largest Pocket wears the Crown: Construction of Money Politics and its Regulation in Nigeria (Journal of Management and Social Sciences, 2025)
Nigeria is acknowledged to have an outwardly ambitious and comprehensive political party finance regulatory framework. Evidence in the recent past however points to the ineffectiveness of these elaborate regulatory regimes. This study seeks to offer explanation for the apparent failure of the existing regulatory instruments of party financing to produce intended outcomes. Anchored on the assumptions of the stakeholder theory and using a qualitative research design, the study finds that a number of factors conspire to compromise the regulatory system. In conclusion, the paper proposes some measures that are capable of strengthening the regulatory framework for enhanced effectiveness.